2020
DOI: 10.12688/f1000research.21702.3
|View full text |Cite
|
Sign up to set email alerts
|

High vaccination coverage and inadequate knowledge: Findings from a community-based cross-sectional study on Japanese Encephalitis in Yangon, Myanmar

Abstract: Background: Japanese encephalitis (JE) is a mosquito-borne disease with high case fatality and no specific treatment. Little is known about the community’s (especially parents/guardians of children) awareness regarding JE and its vaccine in Yangon region, which bears the highest JE burden in Myanmar. Methods: We conducted a community-based cross-sectional study in Yangon region (2019) to explore the knowledge and perception of parents/guardians of 1-15 year-old children about JE disease, its vaccination and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Studies reported earlier could hardly verify the vaccine doses using the vaccination cards, as they were not available to estimate vaccination coverage in India 11,12 ; with only half of the guardians having vaccination cards with them outside India. 13 A few JE cases were reported among adults from the study areas earlier indicating the shift of JE and AES cases from children to adult age groups. 10 Some study groups have also noticed a similar shift from children to adult populations in other areas in India.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Studies reported earlier could hardly verify the vaccine doses using the vaccination cards, as they were not available to estimate vaccination coverage in India 11,12 ; with only half of the guardians having vaccination cards with them outside India. 13 A few JE cases were reported among adults from the study areas earlier indicating the shift of JE and AES cases from children to adult age groups. 10 Some study groups have also noticed a similar shift from children to adult populations in other areas in India.…”
Section: Discussionmentioning
confidence: 86%
“…We could verify the vaccination details from the vaccination card provided by parents in most children and additional records maintained by healthcare workers. Studies reported earlier could hardly verify the vaccine doses using the vaccination cards, as they were not available to estimate vaccination coverage in India 11,12 ; with only half of the guardians having vaccination cards with them outside India 13 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Interview with Trader, 6 May 2016).Socio-moral obligations and economic incentives coalesced, reinforced by a strategic reinterpretation of Buddhist charity by state propaganda and religious figures. Official religious teachings used in trainings by the junta-organised welfare group, Union Solidarity and Development Association (USDA), connected Buddhist notions of charity (B: dana ) to the “building of an ideal state” (Kyaw Htut, 1994: xi). From the early 1990s, prominent Buddhist monks including Sitagu Sayadaw also engaged in social welfare activities aimed at meeting the dire needs of people during rapid socio-economic change.…”
Section: Section Two: Political Consequences Of Post-1988 Junta Reformsmentioning
confidence: 99%